Spectrum of Invasive Yeast Infections in Neonates, Children and Adults in Pakistan Over Five Years: 2015-2019 - Rattani, Salima; Memon, Saba; Jabeen, Kauser; Farooqi, Joveria (Infectious Diseases Journal of Pakistan, 2022)
Background: There is a widening population of hosts susceptible to invasive yeast infections secondary to prolonged hospitalization, immunocompromised, use of medical devices, broad-spectrum antibiotics, and survival of extremely vulnerable populations. Here we describe the changing spectrum of invasive yeast infections in neonates, children, and adults in the last 5 years in Pakistan. Methods: Records of archived yeast isolates from Jan 2015-May 2019 kept at the Aga Khan University Clinical Laboratories, section of Microbiology in Karachi, were retrieved for analysis. Frequencies of different Candida and non-Candida species isolated over the last five years were computed and compared for age groups using chi-square test. Results: A total of 1119 non-duplicate isolates were identified, of which 992 were invasive specimens. Candida species made up 86.7%, 88.2% and 88.1% of all invasive yeasts in neonates, children, and adults, respectively. Rare Candida were most common group in neonates, C. tropicalis predominated in children and C. auris topped the list of invasive yeasts in adults. The distribution of invasive yeasts between neonatal, pediatric and adult age groups was different significantly (p<0.001). Change in spectrum of invasive yeast over the years was significant for neonates (p=0.017), and adults (p=0.003). Fluconazole resistance in yeast isolated from neonates, children and adults was found to be 8%, 23% and 36% respectively. Conclusion: It is essential to monitor the spectrum and antifungal resistance trends of yeast infections in neonates and children as they are the population where there is greatest diversity of invasive species, not limited to Candida species. Key words: Invasive yeast infections, Spectrum, Candida, Aresistance, Neonates, Children, Adults.